Operational Guidance on the Use of Special Nutritional Products in Refugee Populations. Issue 4 (December 2013) - Style, Sarah; Tondeur, Melody; Wilkinson, Caroline; Oman, Allison; Spiegel, Paul; Kassim, Ismail A. R.; Grijalva-Eternod, Carlos; Dolan, Carmel; Seal, Andrew
Background: Stunting, acute malnutrition, and micronutrient malnutrition are persistent public health problems in refugee populations worldwide. In recent years there has been an increase in the availability and use of special nutritional products in emergency and development contexts to help address inadequate nutrient intakes from low-diversity diets. The availability of new special nutritional products, and the decision by the United Nations High Commissioner for Refugees (UNHCR) to use blanket supplementary feeding programs to prevent stunting and anemia, raised new challenges for designing, monitoring, and evaluating nutritional programs. Objective: To develop an Operational Guidance on the use of special nutritional products for the prevention of micronutrient malnutrition, stunting, and acute malnutrition in refugee populations. Methods: A literature review and a series of consultations with technical experts, operational organizations, and field staff were performed over a period of 2 years. The Operational Guidance was finalized and released in December 2011. Results: The Operational Guidance describes six stages for defining nutritional problems and identifying possible solutions; assessing and managing risks; testing acceptability and adherence, program design and implementation; and monitoring and evaluation. Key performance indicators are defined and a working nomenclature for new special nutritional products is described. Conclusions: The UNHCR Operational Guidance has filled an important gap in helping field staff deal with the opportunities and challenges of preventing under-nutrition through the use of new products in blanket supplementary feeding programs. The need for further integration of guidance on selective feeding programs is discussed.